Aspects of explosives detection - Marshall, Maurice; Oxley, Jimmie Carol, 1953- (Elsevier, 2009)
Detection and quantification of trace chemicals is a major thrust of analytical chemistry. In recent years much effort has been spent developing detection systems for priority pollutants. Less mature are the detections of substances of interest to law enforcement and security personnel:in particular explosives. This volume will discuss the detection of these, not only setting out the theoretical fundamentals, but also emphasizing the remarkable developments in the last decade. Terrorist events-airplanes blown out of the sky (PanAm 103 over Lockerbie) and attacks on U.S. and European cities)